2015
DOI: 10.3390/e17053438
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transfer and Pressure Drop Characteristics in Straight Microchannel of Printed Circuit Heat Exchangers

Abstract: Performance tests were carried out for a microchannel printed circuit heat exchanger (PCHE), which was fabricated with micro photo-etching and diffusion bonding technologies. The microchannel PCHE was tested for Reynolds numbers in the range of 100-850 varying the hot-side inlet temperature between 40 °C-50 °C while keeping the cold-side temperature fixed at 20 °C. It was found that the average heat transfer rate and heat transfer performance of the countercurrrent configuration were 6.8% and 10%-15% higher, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…The pressure and temperature can be correlated in the vicinity of the saturation condition using Clapeyron-Clausius equation, which is defined as: dp dT " L T`v g´vl˘ ( 13) in which, L is the latent heat. In this view, the condensation and evaporation rate can be rewritten as:…”
Section: Phase Change Modelmentioning
confidence: 99%
“…The pressure and temperature can be correlated in the vicinity of the saturation condition using Clapeyron-Clausius equation, which is defined as: dp dT " L T`v g´vl˘ ( 13) in which, L is the latent heat. In this view, the condensation and evaporation rate can be rewritten as:…”
Section: Phase Change Modelmentioning
confidence: 99%
“…A trend line was then generated from the simulation results for the first 6 layers. A linear relationship between pressure drop and flow rate might be expected for laminar flow through the channel areas, however the distribution and mix areas of the heat exchanger, as well as the inlet and outlet pipes, may experience turbulent flow, and other studies of micro-channel heat exchangers have observed a 2 nd order polynomial relationship between pressure drop and Reynolds number [22,23]. A 2 nd order polynomial relationship for pressure drop as a function of flow rate, generated from the results of the first 6 simulations, agreed with the results of the simulation for 7 layers, and was thus used to extrapolate to the full 32 layers.…”
Section: Heat Exchanger Pressure Drop Experiments and Simulation A Bementioning
confidence: 99%
“…Several published articles have addressed some relevant experimental and computational issues associated with the performance of various channel shape configurations in heat exchangers, including straight channels 18,19 and zigzag channels 20–22 with design parameters like working fluids and temperature ranges. For example, Annesh et al 23 showed that the trapezoidal channels yielded the highest thermo‐hydraulic performance at the cost of the highest pressure drop in comparison with sinusoidal or triangular channels.…”
Section: Introductionmentioning
confidence: 99%